Crop rotation. XVI. Effects of cropping systems on grain quality and other agronomic characteristics of soybean plants - Santos, Henrique Pereira dos; Vieira, Simião Alano; Pereira, Luiz Ricardo; Roman, Erivelton Scherer (Pesquisa Agropecuaria Brasileira, 1991)
A trial was carried out during the period of 1984-1986 at the National Wheat Research Center - CNPT/EMBRAPA (Passo Fundo, Brazil). The effects of some crop rotation systems on yield and on other agronomic characteristics of soybean (Glycine max. (L.) Merrill) were assessed. Nine cropping systems were tested where soybean were seeded after different winter crops (oats, barley, rapeseed, flax, and wheat) distributed in several crop rotation systems. Soybean was direct-drilled at a randomized blocks design with four replicates, and plot sizes of 120 m2. In the 1984 summer season, with normal precipitation and adequate rates of crop residue decomposition, soybean showed high values for primary yield components and plant height, which reflected directly in grain production. In the relatively dryer years, when the winter crop residues decomposition was slower, grain yield, plant population, plant height and insertion of first pods were afected, mainly after rapeseed.